Literature review of the effects of the adoption of data analytics on gathering audit evidence - Wadesango, N; Muzvuwe, F.T; Malatji, S; Sitsha, L; Wadesango, O (Allied Business Academies, 2022)
Research shows that companies that can effectively utilize big data, on average, have a 5 to 6 per cent higher gain in productivity. The aim of this desktop research was to understand the effects of adopting data analytics on gathering audit evidence. The researchers scrutinised available documents in order to find out what other authors have found out to be the effects of big data and data analytics in gathering audit evidence. This study basically serves as an evaluation of the literature by other scholars who researched on the related field of data analytics. The study looked at data analytics theory, literature review and gap analysis. The two variables of the research which are data analytics and audit evidence were discussed. It emerged that adoption of data analytics have a positive effect on gathering audit evidence. Recommendation is given for KPMG to fully adopt data analytics as solutions to challenges faced when using data analytics.